Budikdamber Training: Efforts to Optimize the Utilization of Home Yard - Cahniyo Wijaya Kuswanto; Bachtiar Rohman; Galuh Yuliar Denata (FOUNDAE (Foundation of Advanced Education), 2022)
Breeding and farming with limited land and does not require significant capital, Budikdamber can be one of the most appropriate choices in overcoming food problems. This Budikdamber activity aims to provide knowledge and training to the Dasawisma group in utilizing home yard land and fostering an entrepreneurial spirit. The method used in this service was a direct practice method carried out by Dasawisma women using tools and materials prepared by the community service team. The participants consisted of 20 people. The activities were carried out by complying with the health protocols. The materials provided were 1) an explanation of Budikdamber (Fish Cultivation in a Bucket), 2) an Explanation of the tools and materials used, and 3) training on how to make Budikdamber. Through this activity, the people of Rukti Sedyo village have learned how to make good and correct Budikdamber techniques.